America's pastor : Billy Graham and the shaping of a nation - Wacker, Grant, 1945- (2014)
Examines the life of Billy Graham and how he impacted American culture by successfully tapping into broader cultural trends.
Preacher -- Icon -- Southerner -- Entrepreneur -- Architect -- Pilgrim -- Pastor -- Patriarch.
Includes bibliographical references (pages 319-396) and index.
Keywords: Graham, Billy, -- 1918-; Christianity and culture -- United States -- History -- 20th century; History